Cover Feature: In Situ Electrochemical Investigations of Inherently Chiral 2, 2′‐Biindole Architectures with Oligothiophene Terminals (ChemElectroChem 17/2021). Issue 17 (1st August 2021) - Malacrida, Claudia; Scapinello, Luca; Cirilli, Roberto; Grecchi, Sara; Penoni, Andrea; Benincori, Tiziana; Ludwigs, Sabine
Abstract : The Cover Feature shows electrooligomerized organic films and highlights their chirality features. More information can be found in the Article by C. Malacrida, L. Scapinello et al .